MULTIMEDIA DEVELOPMENT OF LEARNING ENTREPRENEURSHIP TO INCREASE STUDENT LEARNING OUTCOMES IN THE ECONOMIC EDUCATION STUDY PROGRAM FKIP NUSA CEN DANA UNIVERSITY 2018 (JURNAL ECONOMICA : Research of Economic And Economic Education, 2019)
This research purpose to (1) analyze the validity of multimedia learning in improving student learning outcomes entrepreneurship courses FKIP Nusa Cendana University economics education (2) Knowing the effectiveness of the use of multimedia learning in improving student learning outcomes entrepreneurship courses FKIP economic education Nusa Cendana University. This research is meth od Research and Development (R & D). Data collection techniques used were interviews, questionnaires, tests, and documentation. Results of research and development of multimedia learning create more effective learning, make students more active, and motivate students create creative ideas in learning can improve student learning outcomes. Results posttest values student learning outcomes third semester of economic education courses between class and class control experiments showed that the average yield posttest control group was 65.98 while the average posttest experimental class was 79.52. After the t-test were analyzed using SPSS 21 IBM software obtained a significance value of 0,000 <a (0.05), which showed that the experimental class H1 accepted meaning better than the control class. Based on the results of the value of learning outcomes posttest control group and the experimental class also analyzed by t-test formula. T value obtained from the posttest control class and experimental class is 6.369 with t table value is 1.999. Thus tcount> t table, meaning an increase in the value of the experimental class students learn entrepreneurship better than the control class. This shows that multimedia learning results further enhance the value of entrepreneurship student learning outcomes compared to the no use of multimedia learning. The conclusion from this study is valid multimedia learning to improve learning outcomes and multimedia learning effectively to improve learning outcomes.